Pemanfaatan Media Proprofs sebagai Media Evaluasi Hasil Pembelajaran pada Materi Teks Tanggapan - Eka Silvia (ESTETIK : Jurnal Bahasa Indonesia, 2023)
Evaluation activities are activities that tend to be disliked by students because teachers usually use written tests in the form of multiple choices or entries with long descriptive text. These activities are considered more boring by students than learning activities, because they are required to focus and dwell on monotonous questions. One of the learning evaluation media options is Proprofs. This study aims to describe the utilization of the Proprofs platform as a medium for evaluating learning outcomes in class IX response text material at SMP Negeri 77 Central Jakarta. This study used a qualitative descriptive method through observation and questionnaire techniques with research subjects of class IX students at SMP Negeri 77 Central Jakarta, totaling 40 participants as questionnaire respondents and 10 participants who took the test with Propofs. The results of this study were that the mastery of the students who took the quiz was considered to be lacking in acceptance and understanding of the response text material and many of the students had not been able to achieve the KKM score that had been set. In utilizing and using the Propofs platform, students feel interested in using the Propofs platform as a fun learning evaluation medium.